A novel fluorescent long-chain fatty acid-substituted dye: labeling and biodegrading of Microthrix parvicella. Issue 62 (22nd October 2018) - Gu, Yingchun; Lin, Dayong; Fei, Xuening; Wang, Cuihong; Yang, Qi; Tang, Yalin; Ren, Xueling
Abstract : M. parvicella in situ could be biodegraded by a novel fluorescent probe of carbazole modified by LCFA(FP1). Abstract : Microthrix parvicella ( M. parvicella ) is a filamentous bacterium that induces bulking in activated sludge. Here, we used the affinity of long-chain fatty acids (LCFA) for M. parvicella to create a novel fluorescent probe of carbazole modified by LCFA. The structure was characterized by 1 H NMR spectroscopy and mass spectrometry. The spectral properties, photostability, and hydrophobic properties of the probe were also characterized. Fluorescent-labeling results showed that it can label M. parvicella in situ and could be biodegraded via metabolism. The stable docking mode of carbazole probes with different fatty acid chains and lipases was also docked by the density functional tight-binding (DFTB) method.